Promotional trends and the ratings of the top-five AM stations in Iloilo City. - Velasco, Catherine A.
This research is a descriptive study on the promotional trends and the ratings of the top-five AM stations in Iloilo City. (p)A total of ten respondents were interviewed which include the station managers, area manager, production managers, administrative officer and other station personnel who are directly involved in the decision-making process and formulation of station promotions and gimmicks., The top-five AM stations, except one station owned by the government, adhere to the rating system. They engage in promotional activities designed to gain station awareness, increase audience interest and achieve better ratings. However, some stations doubt the credibility of the rating system due to irregularities in the rating survey. To ensure good ratings, the stations have to concentrate on programming and then devise certain promotions and gimmicks as part of the station's programming efforts.